(untitled) (Islamic Sciences Journal, 2023)
Islamic Law aims to Prevent felonies that result terrifing People and scareing them , It sees the need to save the necessities of life without , It has considered the attack on the necessary interests as a crime because it is one of the Strongest Sharia . Provisions have been initiated to maintain these necessities . A felony may be accompanied by facts or circumstances relating to it or the perpetrator that multiply its gravity and reveal the Seriousness of its Perpetrator and entail an aggravation of the Penalty Prescribed for the crime to the extent exceeding the Prescribed Limit , in order to achieve Security and Stability among People , Any person who stop making erimes , infringes on Society in all forms and means or repeats the crime , he must be treated with a severe Punishment that limits his crime . There are specific causes and circumstances behind increasing any punishment. These circumstances are excluded from the crime. They could precede or accompany it. They could also due to the offenders behavior or beyond it them affect the kind and amonnt of the punishment.